Dynamics of a Global Zoonotic Research Network Over 33 Years (1980–2012). (27th July 2015) - Hossain, Liaquat; Karimi, Faezeh; Wigand, Rolf T.
Abstract: Objective: The increasing rate of outbreaks in humans of zoonotic diseases requires detailed examination of the education, research, and practice of animal health and its connection to human health. This study investigated the collaboration network of different fields engaged in conducting zoonotic research from a transdisciplinary perspective. Methods: Examination of the dynamics of this network for a 33-year period from 1980 to 2012 is presented through the development of a large scientometric database from Scopus. In our analyses we compared several properties of these networks, including density, clustering coefficient, giant component, and centrality measures over time. We also elicited patterns in different fields of study collaborating with various other fields for zoonotic research. Results: We discovered that the strongest collaborations across disciplines are formed among the fields of medicine; biochemistry, genetics, and molecular biology; immunology and microbiology; veterinary; agricultural and biological sciences; and social sciences. Furthermore, the affiliation network is growing overall in terms of collaborative research among different fields of study such that more than two-thirds of all possible collaboration links among disciplines have already been formed. Conclusions: Our findings indicate that zoonotic research scientists in different fields (human or animal health, social science, earth and environmental sciences, engineering) have been actively collaborating with each other over the past 11 years. ( Disaster Med Public Health Preparedness . 2015;9:496–503)